ROLE OF BRAIN NEUROTROPHIC FACTOR IN THE COURSE OF GLAUCOMA - Dildora U.Narzullaeva; Shakhzodbek O.Abdullaev (Central Asian Journal of Medicine, 2024)
Brain-derived neurotrophic factor (BDNF) is one of the important members of the neurotrophic family. Its role is of great importance in the death of ganglion cells in glaucoma. In this review, we would like to highlight the structure, distribution of brain-derived neurotrophic factor, its effect on the survival of retinal ganglion cells and thereby provide a theoretical basis for the neuroprotective treatment of glaucoma.